Correlation of Retinopathy of Prematurity with Oxygen Saturation - S, Praveen; A, Waris (International Journal of Innovative Research in Medical Science, 2021)
Retinopathy of prematurity (ROP) is an abnormal vascular proliferative disease of retina that affects preterm infants. It is a leading cause of childhood blindness worldwide despite improvement in neonatal care and management. Earlier ROP was found to be associated with oxygen therapy only. Now it was concluded that aetiology of ROP was multifactorial but three factors have shown significant association with ROP: low gestational age (GA), low birth weight (BW), prolonged exposure to supplementary oxygen following delivery. Several investigators reported that lower oxygen saturation targets at young post-gestational ages with increased oxygen saturation targets at older post gestational ages reduced the incidence of ROP. However previous clinical studies are not conclusive.